Paths of Socially Shared Regulation of Learning Students in Online Mediated Activities - Pereira, Aluisio José; Gomes, Alex Sandro; Thompsen Primo, Tiago (RENOTE, 2025)
This article aims to analyze the regulation of learning as a practice shared interactively among basic education students when they use digital technologies as a mediating mechanism for learning activities. Labor, material and sensory aspects were explored in a teaching-learning context. Data were collected from 17 elementary and high school students. The analyses allowed us to identify perceptions about the possibility of sharing mutual help experiences and strategies for regulating learning. Evidence of the regulation of learning as a practice distributed between physical and digital spaces and subjects was identified. This influences individual and group attitudes and student engagement.